Propagation of high-energy neutrinos in a background of ultralight scalar dark matter - Reynoso, Matias Miguel (2016)
If high-energy neutrinos propagate in a background of ultralight scalar field particles of dark matter (mφ∼10−23 eV), neutrino–dark matter interactions can play a role and affect the neutrino flux. In this work we analyse this effect using transport equations that account for the neutrino regeneration as well as absorption, and we consider the neutrino flux propagation in the extragalactic medium and also through the galactic halo of dark matter. We show the results for the final flux to arrive on Earth for different cases of point and diffuse neutrino fluxes. We conclude that this type of neutrino interactions with ultralight scalar particles as dark matter can yield very different results in the neutrino flux and in the flavor ratios that can be measured in neutrino detectors such as IceCube.